The Self Who Meets the Other: Deconstructing the “Well-Intentioned” Researcher Through an Ethic of Hospitality - Heringer, Rebeca (Alberta Journal of Educational Research, 2024)
The pursuit of anti-oppressive, cross-racial research has become ubiquitous in educational settings. Although some attention has been given to the complexities such an endeavor involves, more intricate and profound aspects that undergird such projects are revealed when examined through the lens of an ethic of hospitality. Based on a case-study focused on the experiences of Black refugee students in Manitoba, this article deconstructs the research journal that I kept throughout that project. Four overarching and intertwined themes are evidenced and discussed: the methodological decisions I had to make along the study, personal ambivalences experienced, feelings of powerlessness, and the (explicit) implications of my White identity. As such, the research journal here analyzed not only reveals the aporetic nature of hospitality but also several ethical complexities involved in the pursuit of hospitable, anti-oppressive research in a cross-racial setting, which have not received enough attention in current literature. La recherche anti-oppressive et interraciale est devenue omniprésente dans les milieux éducatifs. Bien qu'une certaine attention ait été accordée aux complexités qu'une telle entreprise implique, des aspects plus complexes et plus profonds qui sous-tendent de tels projets sont révélés lorsqu'ils sont examinés à travers le prisme d'une éthique de l'hospitalité. Basé sur une étude de cas centrée sur les expériences d'étudiants réfugiés noirs au Manitoba, cet article déconstruit le journal de recherche que j'ai tenu tout au long de ce projet. Quatre thèmes primordiaux et entrelacés sont mis en évidence et discutés : les décisions méthodologiques que j'ai dû prendre tout au long de l'étude, les ambivalences personnelles vécues, les sentiments d'impuissance et les implications (explicites) de mon identité blanche. Ainsi, le journal de recherche analysé ici révèle non seulement la nature aporétique de l'hospitalité, mais aussi plusieurs complexités éthiques liées à la poursuite d'une recherche hospitalière et anti-oppressive dans un contexte interracial, qui n'ont pas fait l'objet d'une attention suffisante dans la littérature actuelle.